Comparative genomic analysis of Aeromonas dhakensis and Aeromonas hydrophila from diseased striped catfish fingerlings cultured in Vietnam - Erickson, Vera Irene; Khoi, Le Minh; Hounmanou, Yaovi Mahuton Gildas; Dung, Tu Thanh; Phu, Tran Minh; Dalsgaard, Anders (Frontiers in Microbiology, 2023)
Motile Aeromonas septicemia (MAS) is a burden for striped catfish (Pangasius hypophthalmus) farmers in Vietnam. MAS can be caused by several species of Aeromonas but Aeromonas hydrophila is seen as the leading cause of MAS in aquaculture, but recent reports suggest that A. dhakensis is also causing MAS. Here we investigated the bacterial etiology of MAS and compared the genomic features of A. hydrophila and A. dhakensis. We collected 86 isolates from diseased striped catfish fingerlings over five years from eight provinces in Vietnam. Species identification was done using PCR, MALDI-TOF and whole genome sequence (WGS). The MICs of commonly used antimicrobials was established. Thirty presumed A. hydrophila isolates were sequenced for species confirmation and genomic comparison. A phylogenetic analysis was conducted using publicly available sequences and sequences from this study. A total of 25/30 isolates were A. dhakensis sequence type (ST) 656 and 5/30 isolates were A. hydrophila ST 251. Our isolates and all publicly available A. hydrophila isolates from Vietnam belonged to ST 251 and differed with < 200 single nucleotide polymorphisms (SNP). Similarly, all A. dhakensis isolates from Vietnam belonged to ST 656 and differed with < 100 SNPs. The tet(A) gene was found in 1/5 A. hydrophila and 19/25 A. dhakensis. All A. hydrophila had an MIC ≤ 2 mg/L while 19/25 A. dhakensis had MIC ≥ 8 mg/L for oxyteracycline. The floR gene was only found in A. dhakensis (14/25) which showed a MIC ≥ 8 mg/L for florfenicol. Key virulence genes i.e. aerA/act, ahh1 and hlyA were present in all genomes, while ast was only present in A. dhakensis. This study confirms previous findings where A. dhakensis was the dominating pathogen causing MAS and that the importance of A. hydrophila has likely been overestimated. The differences in antimicrobial susceptibility between the two species could indicate a need for targeted antimicrobial treatment plans. The lipopolysaccharide regions and outer membrane proteins did not significantly differ in their immunogenic potentials, but it remains to be determined with in vivo experiments whether there is a difference in the efficacy of available vaccines against A. hydrophila and A. dhakensis.